School Principal Management in Implementing Madrasah Curriculum Operations: Manajemen Kepala Sekolah dalam Melaksanakan Operasi Kurikulum Madrasah - Siregar, Juraida (STAI Publisistik Thawalib Jakarta, 2024)
Damage to the education management system is often caused by ineffective school principal leadership. The success of educational institutions depends greatly on the ability of madrasa heads to carry out management functions such as planning, organizing, directing, and controlling. This research uses qualitative methods by collecting data through interviews, observation, and documentation at State Islamic High School 3 Central Tapanuli. Next, the data was analyzed through the stages of reduction, analysis, and drawing conclusions. The results of this research identify several important points related to management at State Islamic High School 3 Central Tapanuli. First, analyze the role of school principals in improving institutional performance through good leadership. Second, strategic planning involving staff participation contributes to the establishment of clear educational goals. Third, optimal organization with a structured division of tasks increases coordination and operational efficiency. Fourth, inspirational guidance from the madrasa head motivates teachers and staff to contribute optimally. Lastly, regular control ensures that the quality of education is maintained through continuous evaluation and improvement. Overall, this research confirms that the success of educational institutions is highly dependent on the effective implementation of management functions.